Metal–Organic Frameworks (MOFs) Containing Adsorbents for Carbon Capture - Ansone-Bertina, Linda; Ozols, Viesturs; Arbidans, Lauris; Dobkevica, Linda; Sarsuns, Kristaps; Vanags, Edgars; Klavins, Maris (MDPI, 2022)
In this study, new composite materials of montmorillonite, biochar, or aerosil, containing metal–organic frameworks (MOF) were synthesized in situ. Overall, three different MOFs—CuBTC, UTSA‐16, and UiO‐66‐BTEC—were used. Obtained adsorbents were characterized using powder X‐ray diffraction, thermogravimetric analysis, nitrogen adsorption porosimetry, scanning electron microscopy, energy‐dispersive X‐ray spectroscopy, and Fourier transform infrared spectrophotometry. Additionally, the content of metallic and nonmetallic elements was determined to investigate the crystalline structure, surface morphology, thermal stability of the obtained MOF‐composites, etc. Cyclic CO2 adsorption analysis was performed using the thermogravimetric approach, modeling adsorption from flue gasses. In our study, the addition of aerosil to CuBTC (CuBTC‐A‐15) enhanced the sorbed CO2 amount by 90.2% and the addition of biochar (CuBTC‐BC‐5) increased adsorbed the CO2 amount by 75.5% in comparison to pristine CuBTC obtained in this study. Moreover, the addition of montmorillonite (CuBTC‐Mt‐15) increased the adsorbed amount of CO2 by 27%. CuBTC‐A‐15 and CuBTC‐BC‐5 are considered to be the most perspective adsorbents, capturing 3.7 mmol/g CO2 and showing good stability after 20 adsorption‐desorption cycles. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.
This research was funded by the European Regional Development Fund project “Innovation of the waste‐to‐energy concept for the low carbon economy: development of novel carbon capture technology for thermochemical processing of municipal solid waste (carbon capture and storage from waste—CCSW)”, grant number 1.1.1.1/19/A/013.
Keywords: Research Subject Categories::NATURAL SCIENCES; analytical characterization; biochar; carbon capture; CuBTC; desorption; MOF; MOF-composites; montmorillonite; UiO-66-BTEC; UTSA-16